Model Gerak Dasar Berbasis Permainan Untuk Anak Kelas 6 Sekolah Dasar - Dilli Dwi Kuswoyo; Muhammad Nur Fandiasto (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Game-Based Fundamental Movement Models for Year 6 Elementary School Children has a research focus to identify, analyze and produce basic motion model development products. This basic movement model is adapted to aspects of growth and development as well as the characteristics of children which are packaged through physical activity that focuses on manipulative basic movements. This study uses a game-based ADDIE approach for grade 6 elementary school children where later the results of this model can be applied by grade 6 elementary school children in the learning process and recognize various kinds of motion in everyday life. This research is research that refers to the development model as for the steps to be carried out Conduct analysis, Design, Development, Implementation, Evaluation. The results of this study are in the form of a book containing basic motion models for grade 6 elementary school children. The conclusion from this study is that the model developed is in accordance with the characteristics and curriculum materials for grade 6 elementary school children, and is feasible to apply in basic movement learning.